2020
DOI: 10.26487/hjbs.v2i3.350
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Brand Image, Brand Experience and Brand Loyalty towards Purchase IntentionOn Apple Smartphone in Makassar

Abstract: This research aims to analyze the effect of brand image, brand experience, and brand loyalty towards purchase intention on Apple smartphones in Makassar. The method used in this research is a quantitative method using multiple regression. The population in this research was Apple Smartphone users in Makassar; the sample in this research was 100 people. Data collected using questionnaires. This study uses multiple regression analysis statistical tools; the hypothesis tested using the F test (simultaneous) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Past research has suggested that brand loyalty is one of the main factors affecting customers' purchase intention (e.g., Hennig-Thurau, Gwinner, & Gremler, 2002;Keller, 2007;Yaseen & Mazahir, 2019). Chi, Yeh, and Yang, (2009) and Sanjaya, Asdar, and Munir (2020) underlined that purchase intention is positively affected by brand loyalty. According to Yang and Peterson (2004), loyal customers are inclined to buy more than non-loyal customers.…”
Section: Relationship Between Brand Loyalty and Purchase Intentionmentioning
confidence: 99%
“…Past research has suggested that brand loyalty is one of the main factors affecting customers' purchase intention (e.g., Hennig-Thurau, Gwinner, & Gremler, 2002;Keller, 2007;Yaseen & Mazahir, 2019). Chi, Yeh, and Yang, (2009) and Sanjaya, Asdar, and Munir (2020) underlined that purchase intention is positively affected by brand loyalty. According to Yang and Peterson (2004), loyal customers are inclined to buy more than non-loyal customers.…”
Section: Relationship Between Brand Loyalty and Purchase Intentionmentioning
confidence: 99%
“…Past research has indicated that brand loyalty is one of the main factors influencing customers' purchase intention (e.g., Hennig-Thurau, Gwinner, K. P., & Gremler, 2002; Keller, 2007;Yaseen & Mazahir, 2019). Chi, Yeh, & Yang, (2009) and Sanjaya, Asdar, and Munir (2020) underlined that purchase intention is positively influenced by brand loyalty. According to Yang and Peterson (2004), loyal customers tend to buy more than non-loyal customers.…”
Section: Relationship Between Brand Loyalty and Purchase Intentionmentioning
confidence: 99%
“…Saat ini di dalam pasar pariwisata yang bersaing dan sadar akan merek, membangun sebuah brand image di destinasi wisata Saribu Rumah Gadang merupakan pekerjaan yang menantang (Dunuwille & Pathmini, 2016) Brand image adalah cara pandang tentang suatu merek yang tercermin oleh asosiasi merek dalam ingatan konsumen (Keller, 1993) dalam (Gunawan & Wellyantony, 2021) Penelitian terdahulu mengungkapkan Brand Image berpengaruh langsung secara positif dan signifikan terhadap purchase Intention. (Sanjaya et al, 2020).…”
Section: Pendahuluanunclassified